Novel “Perburuan” Karya Pramoedya Ananta Toer dalam Perspektif Latar Sejarah dan Nilai Pendidikan Karakter Serta Relevansinya dengan Pembelajaran Sastra di Sekolah - Bambang Eko Hari Cahyono; Rima Nurmalia; Lisma Meilia Wijayanti (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to describe the historical background and value of character education in the novel "Perburuan" by Pramoedya Ananta Toer and its relevance to literature learning in schools. This research is qualitative descriptive research using a literary sociology approach. The data source is the novel "Perburuan" by Pramoedya Ananta Tour, and several references are related to the study of the novel. The data collection technique is done through document analysis, namely analyzing various documents to formulate the research problem. Data analysis uses flow model analysis with stages of data collection, reduction, presentation, and conclusion. The research results show that the historical setting in the novel studied can be used as a historical document containing the struggle of the Indonesian people against the Japanese colonialists. The novel contains three historical settings: the Japanese occupation of Indonesia, the PETA rebellion, and the independence of the Republic of Indonesia. The novel "Perburuan" contains four character education values: religious values, the value of national spirit or nationalism, the value of love for the homeland, and the value of love of peace. These character education values need to be taught to students through literature learning. The expected result of character education through literature learning is the formation of individuals who behave nobly based on character and example, reflected in students' daily behavior.